The Effect of Using QRIS on The Interest of The People of Banjarmasin City in Giving in The Mosque - Fadhillah, Rizky; Abqory, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
Digital financial technology in Indonesia is now growing, one of which is through the Quick Response Code Indonesian Standard (QRIS). The ease of transactions leads to the emergence of opportunities for some organizations to maximize their benefits, one of which is philanthropic institutions. As an institution that collects funds from the community in the form of infaq so that the use of QRIS is expected to streamline the performance of the institution. Supported by the demographics of Indonesia as a country with the largest Muslim majority in the world so that the use of QRIS as a method of collecting infaq funds has great potential. The purpose of this study was to determine the effect of using QRIS on the interest of the people of Banjarmasin city in giving at the mosque. The research was conducted with a descriptive approach quantitative method with primary data sources from distributing questionnaires to the people of Banjarmasin city. This research was conducted to see the use of QRIS through indicators of benefits, convenience and risk of use against public interest in giving using indicators of internal motivation, social motives and emotional factors. The test results show that the use of QRIS has an effect in fostering public interest so that it has an impact on increasing infaq receipts at the Mosque.